A Review of Foreign Research on Written Corrective Feedback - Zhou, Si (International Journal of Humanities and Education Development (IJHED), 2023)
This paper mainly reviews the empirical research and descriptive research on written corrective feedback in foreign countries. In the introduction part, it mainly clarifies the theoretical and practical needs of the research on corrective feedback in writing. In the theoretical foundation part, it mainly explains some core concepts about errors and corrective feedback and clarifies the research paradigm of error analysis. The key part of this paper is a systematic review of the empirical research and theoretical research on written corrective feedback and provides some implications for the respective research directions of the two types of research in the future. In addition, this paper hopes to provide useful enlightenment for second or foreign language teachers who provide written corrective feedback in their teaching practice.